Effect of Erythrocytes Incubation in Hypertonic Non-Electrolyte Media on their Osmotic Resistance - Nipot, E. E.; Melikhova, S. V.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2006)
Partial K+ loss by cell as a result of hypertonic incubation into 0.8-1.4 M sucrose solution has been established as contributing to an increase in erythrocyte osmotic resistance to hypotonic shock (50 mM NaCl solution). Cell sensitivity to a change in medium osmotic parameters after dehydration in valinomycine-containing non-electrolyte solutions (1mM final concentration) depends on a temperature of hypertonic incubation.